Three-dimensional printed metal-nested composite fuel grains with superior mechanical and combustion properties. Issue 3 (3rd July 2022) - Lin, Xin; Qu, Dandan; Chen, Xuedong; Wang, Zezhong; Luo, Jiaxiao; Meng, Dongdong; Liu, Guoliang; Zhang, Kun; Li, Fei; Yu, Xilong
ABSTRACT: The mechanical and combustion properties of metal-nested composite hybrid rocket fuel grains composed of spiral aluminium (Al) frameworks fabricated using three-dimensional (3D) printing with an embedded paraffin-based fuel were investigated. The mechanical properties of the resulting grains were evaluated by compression tests. In addition, the combustion characteristics of the Al composite grains were examined in a lab-scale hybrid rocket engine with gaseous oxygen as the oxidizer at an initial mass flow rate of 17.9 g/s. Pure paraffin-based (PP) and acrylonitrile–butadiene-styrene (ABS) composite grains were also tested as baseline fuels for comparison. The Al-A composite grain exhibited superior mechanical and combustion properties, with Young modulus, yield stress, and regression rate increased by 757.1%, 381.3% and 52.5% compared with the PP grain. The Young modulus and combustion efficiency were also further improved, by 51.0% and 14.9%, respectively, by including perforations in the spiral blades. These improvements are discussed in detail herein based on experimental data together with numerical simulations. Emission spectra of the engine plumes were also acquired and used to qualitatively analyze the combustion characteristics of the Al blades.